IMPROVEMENT OF MICROPROCESSOR CONTROL OF RAILWAY DECELERATION WAGON DECELERATION DEVICES - Toshbaev Zohid Bahron oglu; Khamdamova Lola Olimjon qizi; Saidov Doston Nuriddin ugli (Galaxy International Interdisciplinary Research Journal, 2021)
Improving the automation and telemechanics control devices of the railway qualifying hill remains one of the most pressing issues today. Several works have been done on the development and modernization of hill automation. However, in the railway sorting fleet, based on the automated microprocessor control method, it is a device that monitors the interruption of routes and approaching the wagon decker, how much weight, how fast it falls and how long the wheel pairs in the wagon decelerator.